Clinical and Sociodemographic Profile of Patients With Thyroid Storm: A National Inpatient Sample Database Analysis - Krueger, Abigail (J Endocr Soc, 2021)
Background: Thyroid storm (TS) is a rare, life-threatening disease that is associated with significant mortality. The clinical outcome of these patients has not been evaluated in general practice on a national scale. Our study aimed to find the clinical characteristics and outcomes of patients admitted to community hospitals with TS using the National Inpatient Sample (NIS) database. Methods: We conducted a retrospective study of adult patients (>=18 years of age) diagnosed with primary and secondary TS from the NIS database from 2012 to 2014. The NIS is the largest all-payer inpatient care database in the United States, containing data on more than seven million hospital stays each year. Statistical analysis performed included Chi-Square test, Wilcoxon two-sample test, Fisher’s exact test and multiple logistic regression with a p-value<0.05 considered significant. Results: In total, 2,163 hospitalizations with TS were identified. The incidence of TS in hospitalized patients was 11.96 per 100,000 hospitalizations. Compared to all other adult hospitalizations reported over the same period, admission with TS was significantly associated with a higher prevalence in African Americans (31.4% vs 14.7%, p<0.001) as well as concomitant blood diseases (31.4% vs 21.9%, p<0.001), drug use disorder (11.4% vs 8.4%, p<0.001), electrolyte disturbance (36.9% vs 23.8%, p<0.001), and psychosis (38.1% vs 28.5%, p<0.001). Admission with TS was associated with lower prevalence of concomitant cancer (2.5% vs 4.9%, p<0.001) and renal disease (5.6% vs 12.2%, p<0.001), along with a higher risk of death during hospitalization (3.9% vs 2.2%, p<0.001). There was no significant association between TS and GI disease, cardiovascular disease, pulmonary disease or rheumatoid arthritis. Admission with TS was associated with longer average length of stay (TS median: 4 days, Non-TS: 3 days, p<0.001) and higher total hospital charge (TS median: $27,360, Non-TS: $24,346, p<0.001). Additionally, TS had a higher incidence in urban populations with large hospitals. Overall, inpatient mortality rate was 3.9%. For those with TS, the odds of inpatient death were greater for age group 30-59 compared to <30 (OR 2.916, p=0.026), age group >60 compared to <30 (OR 3.157, p=0.022), males (OR 2.20, p<0.001), those with cancer (OR 6.42, p<0.001), those with electrolyte disturbance (OR 6.12, p<0.001) and those with a neurologic disorder (OR 2.46, p=0.002). Admitted patients with a concomitant psychological disorder had lower odds of death (OR 0.38, p=0.03). Conclusions: This study identified clinical characteristics associated with TS-related admission including female gender, age 30-59, Caucasian race, and urban populations. Higher mortality was associated with patients 30-59 years and >60 years of age, electrolyte disturbances, blood disease, weight loss, paralysis, cancer, renal disease, and male gender.